Relating constructs of attention and working memory to social withdrawal in Alzheimer's disease and schizophrenia: issues regarding paradigm selection. (February 2019) - Gilmour, Gary; Porcelli, Stefano; Bertaina-Anglade, Valérie; Arce, Estibaliz; Dukart, Juergen; Hayen, Anja; Lobo, Antonio; Lopez-Anton, Raul; Merlo Pich, Emilio; Pemberton, Darrel J.; Havenith, Martha N.; Glennon, Jeffrey C.; et al.
Highlights: Brain diseases are not diagnosed based on neurobiological mechanisms Value may be gained by deep and broad phenotyping across disease states Attention and working memory are important constructs for assessment Assay selection across disease states requires significant compromise Relating psychological construct to functional ability may redefine brain disease Abstract: Central nervous system diseases are not currently diagnosed based on knowledge of biological mechanisms underlying their symptoms. Greater understanding may be offered through an agnostic approach to traditional disease categories, where learning more about shared biological mechanisms across conditions could potentially reclassify sub-groups of patients to allow realisation of more effective treatments. This review represents the output of the collaborative group "PRISM", tasked with considering assay choices for assessment of attention and working memory in a transdiagnostic cohort of Alzheimer's disease and schizophrenia patients exhibiting symptomatic spectra of social withdrawal. A multidimensional analysis of this nature has not been previously attempted. Nominated assays (continuous performance test III, attention network test, digit symbol substitution, N-back, complex span, spatial navigation in a virtual environment) reflected a necessary compromise between the need for broad assessment of the neuropsychological constructs in question with several pragmatic criteria: patient burden, compatibility with neurophysiologic measures and availability of preclinical homologues.